Abnormal lipid metabolism and atherosclerosis: a new perspective on organelle function regulation and ferroptosis - Wu, Xize; Huang, Yuxi; Ren, Jiaqi; Pan, Xue; Wu, Qiuying; Cai, Qicheng; Wang, Ruiying; Feng, Teng; Gao, Shan; Wang, Bo; Cheng, Meijia; Li, Yue; et al. (Frontiers in Immunology, 2025)
BackgroundAtherosclerosis (AS), characterized by lipid accumulation, contributes significantly to global cardiovascular morbidity. Ferroptosis, an iron-dependent form of cell death triggered by lipid peroxidation, is emerging as a critical player in AS progression. Therefore, our study seeks to elucidate the intricate mechanisms of ferroptosis within the lipid metabolism pathway in AS.MethodsDifferentially expressed genes were identified from the GSE100927 dataset, subsequently isolating AS lipid metabolism-related ferroptosis genes (ASLMRFeGs). Unsupervised cluster analysis was performed on AS samples to identify molecular clusters. WGCNA was performed to uncover module Hub genes. Multiple machine learning models (LASSO, SVM-RFE, RF) were applied to screen Hub genes. Experimental validation was performed by ox-LDL-induced HUVECs and RAW 264.7 cells. Single-cell data analyzes the gene structure and gene expression status of individual cells.ResultsSix ASLMRFeGs (CTSB, CYBB, DPP4, HILPDA, HMOX1, IL1B) alter the immune microenvironment in AS. AS samples were stratified into two molecular clusters, exhibiting significant variations in inflammation and immune responses. Enrichment analysis of the 225 module Hub genes showed close association with inflammation, immune responses, cytoskeleton organization, and various organelles. Machine learning identified four candidate Hub genes (TYROBP, CSF1R, LCP2, C1QA). In vitro experiments showed that dysregulated lipid metabolism promotes ferroptosis, and inhibition of ferroptosis improves mitochondrial and lysosomal dysfunction and suppresses endoplasmic reticulum stress. Ferrostatin-1, an ferroptosis inhibitor, attenuated the ox-LDL-induced upregulation of CYBB, HMOX1, IL1B, TYROBP, and CSF1R genes. A nomogram for predicting AS risk was constructed incorporating the expression levels of these five validated Hub genes. Single-cell data analysis results suggested that these genes were highly expressed in foam cells, inflammatory macrophages, smooth muscle cells, and helper T cells.ConclusionIn AS, abnormal lipid metabolism may drive ferroptosis via key regulatory genes (CYBB, HMOX1, IL1B, TYROBP, CSF1R), while also reshaping the immune microenvironment, potentially through the modulation of organelle function.